Free churches and society: the nonconformist contribution to social welfare, 1800 - 2010 - Husselbee, Lesley; Ballard, Paul H. (Continuum, 2012)
Many of the key improvements to social conditions in the United Kingdom have been made by Christians. Most of us would be able to think of such key Anglican figures as William Wilberforce, Anthony Ashley Cooper, Earl of Shaftesbury or Dr Thomas Barnardo, but lesser known contributions were made behind the scenes by significant members of the Non-Conformist Churches. This book traces the Free Church contribution to society from 1800 to the present day. It looks at the work of campaigners, co-operative societies, philanthropists and politicians, and traces the ways in which conditions in slums, education, and industry were improved, including work with women and with black and ethnic minorities. There is a growing interest in the part the churches can play today in community development and in the building of social capital. This book will show that some of the things now seen as government initiatives had their origins in the work of Free Church pioneers.